1982
DOI: 10.3386/w0925
|View full text |Cite
|
Sign up to set email alerts
|

LDC Borrowing with Default Risk

Abstract: This paper presents a theoretical model to describe the effects of default risk on international lending to LDC sovereign borrowers. The threat of defaults in international lending is shown to give rise to many characteristics of the syndicated loan market: (1) quantity rationing of loans; (2) LDC policies designed to enhance creditworthiness; (3) prevalence of short maturities on international loans; and (4) a prevalence of bank lending relative to bond-market lending. Daniel Cohen Jeffrey SachsVisiting (6ii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0
4

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 9 publications
2
70
0
4
Order By: Relevance
“…As noted by Sachs and Cohen (1982), a long-term loan contract would require a higher rate of interest for a given size loan than a shorter term contract to achieve non-negative profits. Borrowers may prefer debt of shorter maturities at lower rates of interest, so that long.…”
Section: Shortening Of Oebt Maturitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted by Sachs and Cohen (1982), a long-term loan contract would require a higher rate of interest for a given size loan than a shorter term contract to achieve non-negative profits. Borrowers may prefer debt of shorter maturities at lower rates of interest, so that long.…”
Section: Shortening Of Oebt Maturitiesmentioning
confidence: 99%
“…AsylTlfTletries of ;~formation about total concurrent indebtedness of borrowers between debtors 3 and creditors are shown to imply the shortened debt maturity structures, predominance of bank over bond lending, relationship between quantity-rationing of credit and rates of investment, and exclusion of the lowest income LDCs from the private international capital market observed in LDC borrowing. Another paper, by Sachs and Cohen (1982), explores the relationship between default risk, the lack of bond covenants and the special features of LDC borrowing. Their approach and explanations differ greatly from those given in this paper, which concentrate on the role of asymmetries of information between creditors and debtors.…”
Section: Introductionmentioning
confidence: 99%
“…Among them were Sachs and Cohen (1982), who modeled default risk on international lending to LDC's. Their study reported how the threat has shaped the international lending landscape.…”
Section: Summary Literaturementioning
confidence: 99%
“…The difference between the prices that the borrower faces after repayment or default can be viewed as a "default premium". Ex-ante such a "default premium" constitutes a deterrent mechanism that induces countries to pay even in the absence of output penalties featuring elsewhere (e.g., Sachs and Cohen, 1985;Obstfeld and Rogoff, 1996;Alfaro and Kanuzck, 2005). Ex-post, however, the attendant rise in spreads associated with such a "default premium" increases the cost of future borrowing.…”
Section: Introductionmentioning
confidence: 99%